PHYSICO-MECHANICAL AND THERMOPHYSICAL PROPERTIES OF EPOXY COMPOSITES FILLED WITH DISPERSED PARTICLES OF OXYTETRACYCLINE - Sotsenko, Vitalii (Scientific Journal "Metallurgy", 2023)
Epoxy binder DER - 331 manufactured by Dow Chemical Comp (Germany) was used to form epoxy composite materials. Cold-cured triethylenetetramine TETA hardener was used to crosslink the epoxy binder (q = 10 pts. wt. by weight per 100 pts. wt. by weight of DER-331 epoxy resin). A tetracycline antibiotic with a dispersion of 5…10 μm was used as a filler. Complex studies of adhesive, physical and mechanical properties were carried out, based on the results of which the optimal content of oxytetracycline in the reactoplastic matrix was established, which is q = 0.5…1.5 pts. wt. per 100 pts. wt. by weight oligomer DER-331 and 10 pts. wt. Theta’s stronghold. Such composites are characterized by the following properties: adhesive tensile strength is σа = 40.0 MPa, destructive bending stresses – σben = 80.0 MPa, flexural modulus – E = 3.3…3.4 GPa, toughness – W = 8.0 kJ/m2. It has been suggested that the increase in mechanical strength of the developed materials is due to the moderate mobility of segments and side groups of composite macromolecules, which provides flexibility of the main chain and, consequently, the elastic characteristics of the polymeric material. Additionally, the study of filled composite materials under the influence of variable temperatures. The dynamics of changes in the thermophysical properties of epoxy composite materials in different temperature ranges (ΔT = 303…473 K) was analyzed. It is shown that composite materials containing oxytetracycline with a content of q = 0.5…1.5 pts. wt. characterized by improved thermophysical characteristics. In particular: Martens heat resistance is – T = 364 K; thermal coefficient of linear expansion over the temperature range (ΔT = 303…323 K) – α = (2.25…2.68)×10-5 K-1; glass transition temperature – Ts = 352…356 K; shrinkage – ΔL = 0.29%.